Pengembangan Dashboard Kependudukan Berbasis Peta Di Kecamatan Berbah Kabupaten Sleman - Cosmas Haryawan; Maria Mediatrix Sebatubun (Pusat Riset dan Inovasi Nasional, 2023)
Berbah is a sub-district currently called kapenawon, in the Sleman regency of the Special Region of Yogyakarta. Berbah District has a fairly large area and is divided into 4 kelurahan. Large areas require integrated management and ease of monitoring various conditions based on location. Some examples of things that need to be monitored include: UMKM production, the development of a pandemic such as dengue fever, agricultural products and others. So far, the data in Berbah sub-district is spread across various applications so that sometimes it is quite difficult to see the condition of the sub-district in a more integrated manner. This service is aimed at providing solutions to these problems by developing a map-based dashboard application for population data in Berbah sub-district. Access to existing data is done using the Restful Web Service API with JSON format data exchange